Transcatheter Aortic Valve Replacement in Aortic Stenosis: a Clinical Case - V. V. Plechev; V. Sh. Ishmetov; A. V. Pavlov; R. E. Abdrakhmanov; T. R. Ibragimov; S. I. Blagodarov; A. R. Gilemkhanov; E. N. Gerasimenko; M. А. Karimov (Креативная хирургия и онкология)
Background. Aortic valve stenosis is common with prevalence of about 0.5 %, peaking in people aged over 70 years mostly due to age-related valve calcification. The year 2002 was marked by the invention and use of the endovascular aortic replacement valve by an A. Cribier’s group of French surgeons. Russian endovascular surgery introduced transcatheter aortic valve replacement in 2009, having since built an extensive experience in this practice. Perioperative mortality in patients under 70 years with no serious comorbidity ranges from 1 to 3 %, however, reaching two-fold 4–8 % in elderly patients. The emergence of minimally invasive technologies offered cure to critical patients, who would merely not get over an open surgery.Materials and methods. This case study provides video recordings of transcatheter aortic valve replacement (Accurate Neo) in transfemoral approach performed for the first time in the Republic of Bashkortostan. Patient K., 70 yo, diagnosis: Atherosclerosis. Aortic valve stenosis. FC III. Complications: aortic valve calcification st. III, CHF II A, FC III, persistent atrial fibrillation, tachysystole. Comorbid: CHD. Exertional angina. FC III. CHF II A, FC III.Results and discussion. Improving the transcatheter valve type facilitates an optimal individual aortic valve selection. Pre-replacement valvuloplasty was performed in all patients. The valve replacement is followed by transoesophageal echocardiography to justify possible aortic valve post-dilatation upon marked paravalvular regurgitation. The implant positioning relative to the aortic valve fibrous crown and mitral valve flaps is precisely controlled with ultrasound.Conclusion. Interventional radiology currently provides high-quality, effective, minimally invasive medical aid even in aortic stenosis patients with multiple comorbidity. In the patient’s denial of open surgery, transcatheter aortic valve replacement represents a sole alternative treatment, also increasing the life expectancy and quality. A wider diversity of available transcatheter devices enables a better personalisation of the biological valve replacement procedure.